Characterization of Fiber Bragg Grating Accelerometer for Underwater Vibration Detection - Juan Michael Kane Gani; Retno Wigajatri Purnamaningsih; Sasono Rahardjo (Postgraduate, University of Mataram, 2024)
In this paper, the results of the characterization of a Fiber Bragg Grating (FBG) Accelerometer for detecting vibrations underwater are reported. The FBG Accelerometer, consisting of three FBGs, is utilized to detect underwater vibrations in three-dimensional directions. A water pump, with positions varied from 0 to 10 cm, is employed as the vibration source. Furthermore, the experimental results are presented in the form of the peak wavelength shift reflected by the FBG (ΔλB) and frequency. From the experiment results, it is shown that with increasing distance, ΔλB decreases linearly with successive gradients of 0.0058 nm/cm; 0.0059 nm/cm; and 0.0045 nm/cm. for FBG X, Y, and Z. It is also shown that with increasing distance, there is a decrease in frequency from 50 Hz for FBGs X, Y, and Z to 39 Hz; 38 Hz; and 40 Hz for FBGs X, Y, and Z respectively.